Studies on Dissipation Kinetics and risk Assessment of Imidacloprid Residues in Tarai Region of Uttarkhand - SRIVASTAVA, R.M.; Josh, Sneha; Ahmad, A.H.; Bohra, G.S. (International Journal of Development Administration Research, 2020)
Dissipation behavior of neonicotinoid insecticide, imidacloprid (Imidacel 17.8 SL), in okra fruit was studied following application at dose 20 g a.i. ha-1 at VRC G.B.P.U.A.T. Pantnagar Uttrakhand, India, showed a initial deposit of 1.027 mg kg-1 imidacloprid in okra fruit samples. The residue level in okra fruit dissipated to 33.008 % of initial deposition after one day and it further declined to 80.817% after 5 days of last spraying. The residues dissipated below detection limit within 7 days in okra fruits. The half life (t½) of imidacloprid in okra fruits was estimated 2.094 days. The residue level went below MRL (0.7mg kg-1 for okra) within 3 days at the recommended dose.